Distribution maps of marine algae from the Iberian Peninsula and the Balearie Islands. XII. Aditions to Focales (Fucopityceae) - Gallardo, Tomás; Pérez-ruzafa, Isabel M. (Botanica Complutensis, 1998)
PÉREZ-RUZAFA. I.M. & GALLARDO, T. 1998. Disíribution maps of marine algaefrom the ¡berian Península and Balearic Islandt Xli? Aditions to Fucales (Fucophyceae). Bol. Complutensis 22: 187-192. New localities for several species of Oída Fecales are indicated. These new sites perform our knowledge about ffie chorology of these species over ffie maps published before in this journal.
Keywords: Distribution; maps; marine algae; Fucales; Fucophyceae